2022
DOI: 10.3389/fpsyg.2022.892603
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Academic Buoyancy and Social Support on English as a Foreign Language Learners’ Motivation in Higher Education

Abstract: Since motivation determines progress in the class, it has a significant role in the field of learning English as a foreign language (EFL), contributing to a successful learning process. Therefore, teachers need to motivate learners to achieve their learning goals and provide them with a meaningful learning process in stressful situations. Two factors are required to successfully overcome challenges in scholastic circumstances, such as academic buoyancy and social support. The former can be a significant elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
1
6
0
2
Order By: Relevance
“…In emotional experiences, they can better choose and apply the more suitable ER strategies (i.e., SS, DC, RA, R, S, R, V, and SS. The findings of [ 32 , 68 ], as well as [ 69 ] confirmed this result. They found that AB and emotions were closely tied and they could foster learners' behaviors.…”
Section: Discussionsupporting
confidence: 64%
“…In emotional experiences, they can better choose and apply the more suitable ER strategies (i.e., SS, DC, RA, R, S, R, V, and SS. The findings of [ 32 , 68 ], as well as [ 69 ] confirmed this result. They found that AB and emotions were closely tied and they could foster learners' behaviors.…”
Section: Discussionsupporting
confidence: 64%
“…In the same line of inquiry, Azarian false (2020) evidence that AB and emotion regulating training are the cause of learners' academic meaning and academic adjustment. The role of AB was also studied from the lens of social support in higher education by Jia and Cheng (2022). This study indicated that AB and social support are integrated, and both of them supported EFL university learners' motivation.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, it is possible to draw the conclusion that higher levels of self-efficacy are associated with higher levels of AB. It was also determined that a connection exists between AB, academic motivation, and social support [ 62 ]. It was clear that the use of social media could boost students' social support as well as their motivation in the classroom [ 4 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is plausible due to the fact that AER, which entails situation selection, developing competences, redirection attention, reappraisal, suppression, respiration, venting, and social support, is directed skillfully in the case of friendly relationships between teachers and learners as well as learners' encouragement in their own evaluation [ 55 , 56 ]. Furthermore [ 62 ], found that learners' levels of self-efficacy, emotional cognitive adjustment, and ability to handle stress all had reciprocal links with one another.…”
Section: Discussionmentioning
confidence: 99%